2021
DOI: 10.2174/0929866528666211118091810
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treatment with Angiotensin-(1-7) Attenuates the Kidney Injury Induced by Gentamicin in Wistar Rats

Abstract: Background: Acute Kidney Injury (AKI), a common disease of the urinary system, can be induced by high doses of gentamicin (GM). The Renin-Angiotensin System exerts a key role in the progression of the AKI since elevated intrarenal levels of Ang II, and ACE activity is found in this condition. However, it is unknown whether oral administration of Ang-(1-7), a heptapeptide that evokes opposite effects of Ang II, may attenuate the renal injuries induced by gentamicin. Objectives: To evaluate the effects of Ang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The concept that Ang-(1-7) may serve as a novel therapeutic agent in mitigating cardiovascular toxicity of xenobiotics is further supported by the recent finding that Ang-(1-7) could reduce rat aortic arch dysfunction induced by the anti-cancer agent doxorubicin [65]. Additionally, Ang-(1-7) mitigated renal injury induced by gentamicin, an aminoglycoside antibiotic [66]. Thus, we propose that co-administration of Ang-(1-7) may represent a novel strategy to mitigate cardiotoxicity of nanoparticles in general as well as PAMAM dendrimers as described in our present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The concept that Ang-(1-7) may serve as a novel therapeutic agent in mitigating cardiovascular toxicity of xenobiotics is further supported by the recent finding that Ang-(1-7) could reduce rat aortic arch dysfunction induced by the anti-cancer agent doxorubicin [65]. Additionally, Ang-(1-7) mitigated renal injury induced by gentamicin, an aminoglycoside antibiotic [66]. Thus, we propose that co-administration of Ang-(1-7) may represent a novel strategy to mitigate cardiotoxicity of nanoparticles in general as well as PAMAM dendrimers as described in our present study.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we propose that co-administration of Ang-(1-7) may represent a novel strategy to mitigate cardiotoxicity of nanoparticles in general as well as PAMAM dendrimers as described in our present study. As Ang-(1-7) is a peptide drug, to improve its biological stability and delivery in vivo, it can be formulated with cyclodextrins or even PAMAM delivery systems, which have been shown to be effective [66][67][68][69]. Furthermore, in clinical trials, Ang-(1-7) appears to be well tolerated and safe to use in humans [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…RAS and KKS components are involved in the development and progression of different forms of AKI [14][15][16][17]. Different works showed that blockade of the classical arm of RAS [18,19,70,71] or activation of the alternative arm of RAS [4,72] attenuates the gentamicin-induced AKI. Regarding KKS, Bledsoe et al [20] showed the activation of B 2 R ameliorated tubular injury induced by gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a leading cause of morbidity and mortality worldwide [1,2]. AKI episodes are characterized by transient kidney dysfunction caused by different etiologies [3][4][5][6]. The use of aminoglycosides (AG), such as gentamicin, to treat life-threaten-ing infections is an important etiological factor of AKI [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin 1-7 decreases oxygen consumption in the thick ascending limb of the loop of Henle and presumably in the proximal tubules as well [161]. Angiotensin 1-7 alleviates AKI in a variety of animal models [162][163][164][165]. However, whether it has a similar effect in humans remains unknown.…”
Section: Angiotensin 1-7mentioning
confidence: 99%